Neuropsychiatric signs and symptoms of Alzheimer's disease: New treatment paradigms. Issue 3 (5th August 2017) - Lanctôt, Krista L.; Amatniek, Joan; Ancoli‐Israel, Sonia; Arnold, Steven E.; Ballard, Clive; Cohen‐Mansfield, Jiska; Ismail, Zahinoor; Lyketsos, Constantine; Miller, David S.; Musiek, Erik; Osorio, Ricardo S.; Rosenberg, Paul B.; et al.
Abstract: Neuropsychiatric symptoms (NPSs) are hallmarks of Alzheimer's disease (AD), causing substantial distress for both people with dementia and their caregivers, and contributing to early institutionalization. They are among the earliest signs and symptoms of neurocognitive disorders and incipient cognitive decline, yet are under‐recognized and often challenging to treat. With this in mind, the Alzheimer's Association convened a Research Roundtable in May 2016, bringing together experts from academia, industry, and regulatory agencies to discuss the latest understanding of NPSs and review the development of therapeutics and biomarkers of NPSs in AD. This review will explore the neurobiology of NPSs in AD and specific symptoms common in AD such as psychosis, agitation, apathy, depression, and sleep disturbances. In addition, clinical trial designs for NPSs in AD and regulatory considerations will be discussed.